FIND THE ANSWERS

Y = e^-kt(Acosh qt + B sinh qt).Show that y(t)satisfies: d^2y/dt^2 + 2k dy/dt + (k^2- q^2)y = 0?

Answer this question

Do you know the correct answer? Make money answering questions! Join now.
  • Y = e^-kt(Acosh qt + B sinh qt).Show that y(t)satisfies: d^2y/dt^2 + 2k dy/dt + (k^2- q^2)y = 0?


Answers

Y = e^-kt(Acosh qt + B sinh qt).Show that y(t)satisfies: d^2y/dt^2 + 2k dy/dt + (k^2- q^2)y = 0? Find answers now! No. 1 Questions & Answers Place. More ...
Read more
Positive: 57 %
Find right answers right now! Y = e^-kt(Acosh qt + B sinh qt).Show that y(t)satisfies: d^2y/dt^2 + 2k dy/dt + (k^2- q^2)y = 0? More questions about Science ...
Read more
Positive: 54 %

More resources

if y=e^(-kt)[Acosh(qt)+Bsinh(qt)] where A,B,q and k are constant show that d^2y/dt^2+2kdy/dt+(k^2-q^2)y=0 ... looking for steve asap - if sinh(y)=[4sinh(x ...
Read more
Positive: 57 %
... (dy/dt). 2 that satisfies the given conditions ... (t) = C e kt in Eq.1. it may turn out that no ... . so) \037) dy .(b) Show that y(x) = -x 4 if x < 0 ...
Read more
Positive: 52 %
Elementary Differential Equations 6th Edition ... Thus a postedU. o denotesthe initial Y (t = 0) ... y = O. (b) Show f ever in Yp(x)
Read more
Positive: 38 %
Elementary Differential Equations 6th Edition ... = W g = 444.8N2 9. o denotesthe initial Y (t = 0) ... Show that xo(t) (b) Show by induction on n
Read more
Positive: 15 %